Efficacy of SAT2 Foot-and-Mouth Disease Vaccines Formulated with Montanide ISA 206B and Quil-A Saponin Adjuvants - Ntungufhadzeni M. Rathogwa; Katherine A. Scott; Pamela Opperman; Jacques Theron; Francois F. Maree (Vaccines, 2021)
The effective control of foot-and-mouth disease (FMD) relies strongly on the separation of susceptible and infected livestock or susceptible livestock and persistently infected wildlife, vaccination, and veterinary sanitary measures. Vaccines affording protection against multiple serotypes for longer than six months and that are less reliant on the cold chain during handling are urgently needed for the effective control of FMD in endemic regions. Although much effort has been devoted to improving the immune responses elicited through the use of modern adjuvants, their efficacy is dependent on the formulation recipe, target species and administration route. Here we compared and evaluated the efficacy of two adjuvant formulations in combination with a structurally stabilized SAT2 vaccine antigen, designed to have improved thermostability, antigen shelf-life and longevity of antibody response. Protection mediated by the Montanide ISA 206B-adjuvanted or Quil-A Saponin-adjuvanted SAT2 vaccines were comparable. The Montanide ISA 206B-adjuvanted vaccine elicited a higher SAT2 neutralizing antibody response and three times higher levels of systemic IFN-γ responses at 14- and 28-days post-vaccination (dpv) were observed compared to the Quil-A Saponin-adjuvanted vaccine group. Interestingly, serum antibodies from the immunized animals reacted similarly to the parental vaccine virus and viruses containing mutations in the VP2 protein that simulate antigenic drift in nature.